Improved Photovoltaic Performance of CsPbI2Br Perovskite Films via Bivalent Metal Chloride Doping - Qiao, Hong Wei; Chen, Mengjiong; Zhou, Ziren; Cheng, Qilin; Hou, Yu; Yang, Hua Gui (Frontiers in Energy Research, 2021)
Cesium-based all-inorganic perovskite absorbers have attracted increasing attention due to their superior thermal stability, compared to their organic-inorganic counterparts. Up to now, it is a challenge to fabricate high-efficiency all-inorganic perovskite solar cells (PSCs) with low defect densities. Herein, we used bivalent metal chloride salts (SrCl2 and NiCl2) to optimize CsPbI2Br films. The experimental results indicate that this method could deliver high-quality films with improved electronic property. As a result, the champion device based on 0.01M SrCl2 doped CsPbI2Br film achieved a power conversion efficiency (PCE) of 16.07% with a high open voltage (VOC) of 1322 mV, which is about 18% higher than the pristine device.